2009
DOI: 10.1189/jlb.0509309
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cdk9 T-loop phosphorylation in resting and activated CD4+ T lymphocytes

Abstract: The cellular kinase complex P-TEFb is composed of Cdk9 and cyclin T, and it is required for expression of most protein-coding genes by RNAP II. Cdk9 has been shown recently to be activated in cis by autophosphorylation of Thr186 in its T-loop. Using a phosphospecific Cdk9 antibody, we examined the level of Cdk9 T-loop phosphorylation in resting and activated CD4(+) T lymphocytes. Cdk9 T-loop phosphorylation was found to be low-to-undetectable in resting CD4(+) T lymphocytes, and upon activation by distinct sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 28 publications
5
83
1
Order By: Relevance
“…As a positive control for CycT1 and pCDK9 expression, we examined the levels of both proteins in Jurkat cells with or without TNF-␣ stimulation. In agreement with previous findings (33,38,53,70), Jurkat cells had high endogenous levels of CycT1 and pCDK9 that were not affected by TNF-␣ stimulation, while resting memory T cells had low levels of nuclear CycT1 and pCDK9 that increased dramatically following overnight incubation with anti-CD3/anti-CD28 beads (Fig. 6).…”
Section: Tnf-␣ Reactivates Latent Virus In Hpcs Through An Nf-bdependsupporting
confidence: 81%
“…As a positive control for CycT1 and pCDK9 expression, we examined the levels of both proteins in Jurkat cells with or without TNF-␣ stimulation. In agreement with previous findings (33,38,53,70), Jurkat cells had high endogenous levels of CycT1 and pCDK9 that were not affected by TNF-␣ stimulation, while resting memory T cells had low levels of nuclear CycT1 and pCDK9 that increased dramatically following overnight incubation with anti-CD3/anti-CD28 beads (Fig. 6).…”
Section: Tnf-␣ Reactivates Latent Virus In Hpcs Through An Nf-bdependsupporting
confidence: 81%
“…In resting memory CD4 + T cells, which form the bulk of the latent HIV reservoir (32), P-TEFb is not yet formed (33,34). In these quiescent cells, CycT1 is largely absent and CDK9 is found in the cytoplasm (35,36), where it is thought to be in an immature, inactive state. Here we demonstrated that in resting CD4 + T cells Hsp90/Cdc37 stabilizes the basal expression of CDK9 prior to the elevation of CycT1 protein levels.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of these cells leads to significant induction of cyclin T1 protein levels, primarily by a posttranscriptional mechanism (33,38). Similarly, pCDK9 levels are considerably upregulated upon activation (30). In this study, we wished to determine if P-TEFb shows a similar pattern of regulation in naïve and quiescent memory CD4 ϩ T cells that were either uninfected or latently infected with HIV-1.…”
Section: Expression Of P-tefb In Naïve and Central Memory Cd4mentioning
confidence: 99%
“…While the total levels of CDK9 remain relatively constant through resting versus activated states, the levels of T-loop-phosphorylated CDK9 (pCDK9) are very low in resting CD4 ϩ T cells due to the action of the phosphatase PPM1A (29,30). However, activation of these cells induces phosphorylation of the CDK9 T loop by an activating kinase that has recently been shown to be CDK7 (31).…”
mentioning
confidence: 99%